Taxonomic revision of the genus Trichopoda Berthold, 1827 (Diptera: Tachinidae: Phasiinae), with emphasis on the Neotropical fauna - Dios, Rodrigo De Vilhena Perez; Nihei, Silvio Shigueo (Zootaxa, 2020)
Trichopoda Berthold, 1827 is a tachinid genus belonging to the subfamily Phasiinae and natively distributed in the Americas. Species of Phasiinae are parasitoids of Hemiptera, especially Heteroptera, and are greatly important as biological control agents. Trichopoda is included in the “Trichopoda typica” group sensu Sabrosky, along with the genera Eutrichopoda Townsend, 1908 and Ectophasiopsis Townsend, 1915a. The genus Trichopoda includes several nominal species, many of which have been synonymized, whereas others have been transferred to different genera. Even though the group is morphologically remarkable for its bright colors and feather-like setae on the hind tibia and is important from an agricultural point of view, there have been no revisionary works dealing with its species. Before the present study, 22 valid species were included in Trichopoda, divided into two subgenera: Galactomyia Townsend, 1908 and Trichopoda s. str. In the current study, 25 species of Trichopoda are considered valid, of which twelve are described as new: Trichopoda (Galactomyia) auricauda sp. n., T. (G.) castannea sp. n., T. (G.) curvicercus sp. n., T. (G.) dupuisi sp. n., T. (G.) elongata sp. n., T. (G.) eupilipes sp. n., T. (G.) goiana sp. n., T. (G.) splendida sp. n., T. (G.) tenebrosa sp. n., T. (G.) tschorsnigi sp. n., T. (G.) urucurytuba sp. n. and T. (Trichopoda) sabroskyi sp. n. We also propose two new synonymies: Trichopoda (Galactomyia) giacomellii (Blanchard, 1966) syn. n. of T. (G.) pennipes (Fabricius, 1781) and T. (G.) nigripes Wulp, 1892 syn. n. of T. (G.) pennipes (Fabricius, 1781); the synonymies of T. ciliata (Fabricius, 1805) and T. haitensis Robineau-Desvoidy, 1830 with T. (G.) pennipes (Fabricius, 1781) are confirmed. We resurrect one species, T. (Galactomyia) limbata (Blanchard, 1966), which was previously synonymized under T. giacomellii (= T. pennipes). We also propose two new subgeneric combinations: T. alipes Wulp, 1892 and T. squamipes Wulp, 1892 are moved from the subgenus Galactomyia to the subgenus Trichopoda. The species aurantiaca Townsend, 1891 is considered as unrecognized within the genus Trichopoda, whereas T. mexicana Macquart, 1846 and T. subcilipes Macquart, 1844 are considered incertae sedis within the tribe Gymnosomatini. Three species are removed from the genus Trichopoda and placed in the genus Homogenia Wulp, 1892: Homogenia apicalis (Wiedemann, 1830), comb. n., H. decisa (Walker, 1853), comb. n. and H. luteipennis (Wiedemann, 1830), comb. n. We provide an identification key to Trichopoda species; due to lack of material, T. flava Röder, 1885 was not included in the key. The compositions of the two subgenera of Trichopoda are redefined for the Neotropical species, whereby all species previously placed in the subgenus Trichopoda by Guimarães, with the exception of T. alipes Wulp, 1892, T. indivisa Townsend, 1897 and T. squamipes, are transferred to the subgenus Galactomyia. On the other hand, the subgeneric placement of the Nearctic species stays the same. We also comment on and try to clarify possible misidentifications, notably for use of species in biological control programs. We present photographs of males and females of all examined species, as well as illustrations of almost all male and female terminalia.